The Impact of Transfer Pricing, Capital Intensity, Thin Capitalization on Tax Avoidance with Sales Growth as Moderating Variabel in Pharmaceutical and Health Companies Listed on Indonesia Stock Exchange 2017-2022 - Widiani, Viny; Trisnawati, Estralita (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
In Indonesia, current tax regulations aim to address these practices through rules like transfer pricing, restrictions on interest deductions on loans from affiliated companies (thin capitalization rules), and asset depreciation rules. However, companies often seek loopholes or new strategies to reduce their tax obligations. This study aims to evaluate the impact of transfer pricing, capital intensity, and thin capitalization on tax avoidance practices in the health and pharmaceutical sector in Indonesia. This is particularly relevant as health sector companies listed on the Indonesia Stock Exchange saw an average revenue increase of 6% during the overall economic downturn caused by the Covid-19 pandemic, reflecting the growing public awareness of health importance and efforts to maintain health during the pandemic. The data for this study is obtained from the financial statements of health and pharmaceutical sector companies listed on the Indonesia Stock Exchange from 2017 to 2022, selected through purposive sampling, with a total of 132 observations sourced from www.idx.co.id. The analysis method used was panel data regression analysis, with Gross Profit Margin (TA_GM) used as a proxy. The results show that transfer pricing, capital intensity, and thin capitalization have a positive impact on tax avoidance. However, sales growth does not enhance the influence of these independent variables on tax avoidance. These findings are expected to assist the Tax and Financial Services Authority in enhancing regulations related to tax avoidance in Indonesia, aligning with the reduction of tax avoidance practices in the health and pharmaceutical sector, and increasing state tax revenues.